Auditives Dekodierungstraining zur Unterstützung der Dolmetscherausbildung: Die Rolle der deutschen Sprachvarietäten und der neuen Technologien - Miriam Morf (Linguistik Online, 2024)
The paper aims to propose a reflection on the importance of German varieties in the preparation of interpreters. Like many other languages, German is classified as a pluricentric language, i. e. a language officially spoken in more than one centre or nation. This makes it a very variegated language that boasts a multitude of both standard and non-standard varieties. The task of interpreters who choose German as a foreign language is therefore to be able to understand and translate into another language what is spoken by native speakers of German, many of whom, according to the previous statement, often speak different varieties. To do this, the interpreters’ preparation must consider the inclusion of the different language varieties of both standard and non-standard German, especially at the level of auditory decoding, in order to facilitate the understanding of the message at a receptive level. Starting from the definition of a pluricentric language, this contribution will highlight the main difficulties of interpreters at the level of listening comprehension, most of which are found at the level of auditory decoding, before proposing training aimed at decoding the different varieties of standard and non-standard German realised through the use of new technologies.